The impacts of the Covid-19 pandemic on food accessibility and food security (a case study in Central Java) - Dewanti, Rizki Puspita; Indreswari, Rysca; Adi, Raden Kunto; Paryanto, Edi; Ningsih, Hardian; Suryaningrum, Dyah Ayu; Arifin, Zainal; Rachmadhan, Aditya Arief (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: The COVID-19 pandemic has significantly impacted food security and accessibility in Central Java Province. This study aims to analyze the effects of the pandemic on food accessibility in three dimensions—physical, economic, and social—and on food security. Methods: The study was conducted in five cities and regencies with high COVID-19 case rates. The research method employs Structural Equation Modeling-Partial Least Square (SEM-PLS) to identify relationships between latent and manifest variables. Primary data were collected from 348 respondents, while secondary data were obtained from relevant agencies. Results: The findings reveal that the COVID-19 pandemic situation indirectly positively affects food security through improved physical access to food, supported by government policies such as large-scale social restrictions (PSBB) and community activity restrictions (PPKM), which allowed markets to operate with health protocols. However, economic and social access to food was not significantly impacted by the pandemic. Physical access was shown to have a direct positive impact on food security, while economic access was highly influenced by the respondents’ economic conditions. Conclusion: In conclusion, food accessibility—particularly physical access—plays a crucial role in maintaining food security during the pandemic in Central Java.